PLANNING OF GUMANTI MINI HYDRO POWER PLANT (MHPP), SOLOK REGENCY, WEST SUMATERA - Prahasta, Deustin
The Gumanti Mini Hydro Power Plant (PLTM) utilizes the flow of the Batang Gumanti River with a watershed area of 176,94 km2, with the aim of increasing the ratio of Renewable Energy (EBT) usage in West Sumatra and Indonesia. In planning the Gumanti PLTM, rainfall data from the Danau Diatas Station was analyzed for the period 2003-2021 (20 years), resulting in a planned flood discharge for a Q50 year recurrence period of 418,28 m3/s. The NRECA model was used to analyze the dependable discharge, resulting in a Q50% dependable discharge of 6,50 m3/s. The planning of the Gumanti PLTM includes planning for a weir, intake, desilting basin, headrace, forebay, penstock, turbine, and tailrace. Based on topographic conditions and headloss calculations, the effective head at the Gumanti PLTM is 95,09 m with a potential generating capacity of 5,55 MW and an annual energy potential of 34,75 MW. The estimated budget required for the construction of the Gumanti PLTM is IDR 38,73 Billion.